2020
DOI: 10.1002/num.22618
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and mathematical analysis of induction motor by means of AB–fractal–fractional differentiation actuated by drilling system

Abstract: The quality of electric induction motors for its high number of applications can be compared with traditional motor for the check of accuracy of physical and psychological discomforts. A mathematical analysis is performed to study the chaotic phenomena of drilling system actuated by induction motor by means of newly defined fractal–fractional differentiations. The mathematical modeling is described by focusing the drilling system consisting of two disks connected to each other by a steel string in which upper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Our future studies would include the use of Markov Chain Monte Carlo sampling technique for data fitting process to obtain the unknown biological parameters of the model with associated 95% credible intervals. Moreover, non-local time derivatives recently introduced in ( Caputo, 1996 ; Atangana & Baleanu, 2016 ; Caputo & Fabrizio, 2015 ; Atangana, 2017 ) and successfully used in various real life situations (see, for instance ( Atangana & Qureshi, 2019 ; Abro & Atangana, 2020 ; Ahmed et al, 2020 ; Atangana & Atangana, 2020 ; Baleanu et al, 2020 ; Naik et al, 2020 ; Ozair et al, 2020 ; Zarin et al, 2020 )), and will be taken under consideration to comprehend the dynamics of underlying epidemic in more detail.…”
Section: Discussionmentioning
confidence: 99%
“…Our future studies would include the use of Markov Chain Monte Carlo sampling technique for data fitting process to obtain the unknown biological parameters of the model with associated 95% credible intervals. Moreover, non-local time derivatives recently introduced in ( Caputo, 1996 ; Atangana & Baleanu, 2016 ; Caputo & Fabrizio, 2015 ; Atangana, 2017 ) and successfully used in various real life situations (see, for instance ( Atangana & Qureshi, 2019 ; Abro & Atangana, 2020 ; Ahmed et al, 2020 ; Atangana & Atangana, 2020 ; Baleanu et al, 2020 ; Naik et al, 2020 ; Ozair et al, 2020 ; Zarin et al, 2020 )), and will be taken under consideration to comprehend the dynamics of underlying epidemic in more detail.…”
Section: Discussionmentioning
confidence: 99%
“…Finite Fourier sine transform, Laplace, and fractional techniques have been utilized to the governing equations for exhibiting typical and rheological properties of the problem. Although the studies on heat and transfer analysis can be continue yet the relevant studies can be observed therein in categorical format as heat transfer via analytical approaches [16][17][18][19][20][21][22][23], heat transfer via numerical approaches [24][25][26][27][28][29], heat transfer via fractional calculus approaches [30][31][32][33], and heat transfer via multi-dimensional approaches [34][35][36][37]. Motivating by the above consideration, the main theme of this manuscript is to have the significance of convective heating and variable heat source on Azimuthal oscillatory MHD convective flows developed in a cylindrical Darcy-Forchheimer porous medium filled by a radiating second-grade fluid.…”
Section: Introductionmentioning
confidence: 99%
“…e proposed stochastic paradigms can be explored in the future to present the numerical solutions of the nonlinear mathematical systems [52][53][54][55][56][57][58][59][60][61].…”
Section: Data Availabilitymentioning
confidence: 99%